Pemilu Berintegritas dan Malpraktik Pemilu - Mudjiyanto, Bambang; Launa, Launa; Mansur, Mochammad (Jurnal Communitarian (Prodi Ilmu Politik), 2024)
ABSTRACTElection malpractice is a frightening specter in democratic countries. As aconsequence, election integrity is often violated in the electoral process. This studyseeks to discuss the political dynamics of the concepts of electoral malpractice andelection integrity in an electoral setting in a flawed democratic regime withprocedural characteristics. Election malpractices which are widely practiced inflawed democratic regimes have been proven to not only distort the quality ofelections with integrity, but also slowly have the potential to kill democracy. In thepractice of elections that lack integrity, it is difficult to find a fair electoral process, which is free from interference and interference from the authorities. By using asearch of relevant literature, the concept of electoral malpractice is an integral partof the concept of political science which is characterized by illusion. It has thepotential to continue to disrupt the electoral process. It will be intertwined with thenature of populist autocratic regimes, weakening mass media and social networks tomobilize change. In fact, electoral malpractice has distorted the principles offreedom, fairness and competition of elections with integrity. Only through credibleand legitimate election channels, elections with integrity and quality democraticperformance will be realized.Keyword: election integrity, election malpractice, flawed democracy, undemocraticregimes